The Usual Suspects: Does Risk Tolerance, Altruism, and Health Predict the Response to COVID-19? - Ketki Sheth; Greg C. Wright (Center for Economic Studies and ifo Institute (CESifo), 2020)
Using a registered pre-analysis plan, we survey college students during California's Stay-at-Home order to test whether compliance with social distancing requirements depends on key parameters that affect their marginal benefit from doing so. We find a quarter of students violated the order. Yet, neither risk preference, altruism, nor preexisting health conditions were predictive of compliance. Our findings raise doubt about the efficiency of minimally enforced social distancing policies, as well as commonly assumed motivations for compliance. Our results also imply that that those with pre-existing health conditions may not voluntarily comply, resulting in higher health care congestion than otherwise expected.
Keywords: I10; D80; 330; COVID-19; risk; altruism; health